2008
DOI: 10.1093/ejechocard/jen124
|View full text |Cite
|
Sign up to set email alerts
|

Age dependency in the timing of mitral annular motion in relation to ventricular filling in healthy subjects: Umea General Population Heart Study

Abstract: Sequential prolongation of IVRT with ageing reduces LDTD, thus converging the peaks of A(m), A, and Ar (atrial mechanical alignment)-a potential novel method to identify subjects at increased dependency on atrial contraction for late-diastolic filling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…However, interestingly, we found that in group 5, EDTD decreased substantially compared to other groups. These findings were in partial agreement with previous studies 4,8,23 . The substantial decrease in EDTD in group 5 might be caused by reduced LV relaxation (i.e.…”
Section: Early Diastolic Phasesupporting
confidence: 93%
“…However, interestingly, we found that in group 5, EDTD decreased substantially compared to other groups. These findings were in partial agreement with previous studies 4,8,23 . The substantial decrease in EDTD in group 5 might be caused by reduced LV relaxation (i.e.…”
Section: Early Diastolic Phasesupporting
confidence: 93%
“…The a’ velocity is a fast and accurate marker of atrial systolic function and correlates with other measures of LA function [ 20 , 21 , 22 , 31 ]. Preclinical atrial dysfunction is characterized by reduced reservoir and conduit function, while atrial contractile function remains normal.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the lack of invasive assessment may hinder the evaluation of the accuracy of our findings regarding LAVi/a’ versus cardiac catheterization. However, the inverse correlation of TDI-a’ with LVFP has been previously demonstrated, as well as its relationship with worse DD grades [ 5 , 20 , 21 , 22 ]. Thus, though future invasive studies focused on the relationship between LAVi/a’ and LVFP would be welcome, we do not think their absence may flaw our data or their interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If such patients develop atrial fibrillation, the isolated late diastolic filling component will be shifted to early diastole but at the expense of raising the left atrial pressure and reducing the stroke volume. 4,5 patients with Q wave infarction. 7 Left ventricular filling pattern could also be affected by other electric abnormalities.…”
Section: Age and Diastolic Functionmentioning
confidence: 99%